The Future Role of Renewable Energy Sources for the Generation of Electricity in the European Region - Pedraza, Jorge Morales (Journal of Reviews on Global Economics, 2014)
The development and use of renewable energy sources for electricity generation, particularly energy from wind, hydro, solar, biomass and geothermal, is a central aim of the European Commission’s Energy Policy. For this reason, it is important to know what could be the role that renewable could play within the EU energy mix during the coming years, based on the role that this type of energy sources is now playing. The use of renewable energy sources for the generation of electricity is expected to be economically competitive in comparison with the use of conventional energy sources with the same purpose, will reduce the negative impact on the environment and the population as a result of the burn of fossil fuels, and will reduce the cost of the energy bill in the medium to long-term.